âPengaruh Suhu, Ketebalan Bahan dan Perbedaan Jumlah Penggilingan Pada Kinetika Pengeringan Lapis Tipis Limbah ikan menjadi Tepung Ikan - , RISTAWANI, S.Pd, Wiratni, S.T., M.T., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Drying process is a sequence step of fish meal production with the dry method. This research has the purpose to study the effect of various variables in the drying process of fish waste i.e. the number of milling steps, material thickness and the drying temperature to predict the characteristic of drying process by determining the drying coefficient, effective diffusivity and activation energy from the sample of fish waste produced. The coefficient determining is used for deciding the drying model. Thin layer drying process was done with drying air at the temperature of 55, 60, 70 dan 80oC, the thickness variation were 5, 10, 15, 20, 25 and 30 mm the other variation is the steps number of milling i.e. 1 step and 3 steps to the fish waste. The experiment was started by milling the wet fish waste, to put the milled fish waste to the molding up to certain thickness and to measure the weight of the wet fish waste. The dryer was started tested at the certain temperature. After the desired temperature was achieved the fish waste was entered to the dryer, the dryer was closed and the process was started. Every hour the sample was taken to be measured the weight. The process was stopped when the weight was constant. The drying coefficient for all drying condition obtained were 0,032-0,489 per hour. The effective diffusivity at the falling rate period was 3,02x10-7 - 1,83x10-5 m2/jam and at the second falling rate 4.16x10-7- 5,69x10-5m2/jam . The activation energy was 1347,69-2815,9 for 1 step of milling and 815,2-2327,08 for 3 step of milling. The final conclusion shows that at the thickness of 5, 10 dan 15 mm were highly affected by the drying temperature by determining the drying model with the Arrhenius approach. The fish meal quality produced were the water content as 7,56%, protein content as 44,87%, the ash content as 16,95%, and fat content as 29,28%